(The Effect of Weathering and Rolling on Drying of Cat's Whiskers (Otrhosiphon stamineus benth) Leaf - H Guring Pohan; Endah Djubaedah; Noerdin N.K (Balai Besar Industri Agro, 1999)
A study on the drying of cat's whiskers leaf (Orthosiphon staminues benth has been carried out. the treatment of this study were A) fresh leaf weathered, rolled and then dried. the analysis of dried cat's whiskers leaf include: yield, color, moinsture, ash, potassium, extract and sinensetin content. the result of dried leaf analysis showed the yield 18.09%, ash 12.09%, extract content 21.43% and senensetin 1.47% at the treatment of D (fresh leaf weathered, rolled and the dried) compared with another treatment and the color is slightly brown. the lowes the moinsture was 8.66% at the treatment of A (fresh leaf were dried directly).